2011
DOI: 10.1159/000324114
|View full text |Cite
|
Sign up to set email alerts
|

Change in HER-2/neu Status from Negative to Positive following Treatment in Breast Cancer: A Case Report

Abstract: Introduction: Approximately 25–30% of breast cancers are assumed to be HER-2/neu positive. It is well known that HER-2/neu-positive cancers after treatment with trastuzumab can become HER-2/neu negative. Change in HER-2/neu status from negative to positive following treatment has not been well studied. We describe a patient with inflammatory breast cancer who was initially HER-2/neu negative but became positive after treatment. A 59-year-old postmenopausal white female saw her surgeon for violaceous discolorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…Although there is no target therapy HER2 breast cancer patients in Rwanda, the use of hormonal therapy was showing effective in patients expressing HR(s). This is may be linked to the previous studies that reported the change from HER2 + to HER2- [34], leading to negative patients' prognosis [44], or with no impact on the prognosis [45]. The worse situation of lacking the HER2 inhibitor targeted therapy, such as trastuzumab to manage HER2 breast cancer patients [46] could be likely resolved by the conversion of HER2+, the opposite situation could also happen which yet require to include the HER2 targeted therapy in the treatment options.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Although there is no target therapy HER2 breast cancer patients in Rwanda, the use of hormonal therapy was showing effective in patients expressing HR(s). This is may be linked to the previous studies that reported the change from HER2 + to HER2- [34], leading to negative patients' prognosis [44], or with no impact on the prognosis [45]. The worse situation of lacking the HER2 inhibitor targeted therapy, such as trastuzumab to manage HER2 breast cancer patients [46] could be likely resolved by the conversion of HER2+, the opposite situation could also happen which yet require to include the HER2 targeted therapy in the treatment options.…”
Section: Discussionsupporting
confidence: 54%
“…The expression of HER2 breast cancer was also found in 31% of the study population. This nding showed that HER2 positivity is slightly falling in the range of reported literatures (15-30%) [9,[33][34][35][36][37]. For instance, Borgquist et al…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, Taucher et al analyzed tumors of patients on anthracycline/taxane-based neoadjuvant therapy regimens and found no significant change of HER2/neu expression, 13 and Sivarajan et al reported a case showing conversion from HER2/neu negative to positive. 27 Thus, the findings in reported NAC studies are conflicting with respect to HER2/neu status and response to anthracyclines. However, based on our results we recommend that the HER2/neu IHC score should be reevaluated in posttreatment tissue, as clinical decisions regarding adjuvant cytotoxic treatment after NAC are frequently based on immunohistochemical analysis performed on surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HER2 breast cancer was also found in 31% of the study population. This finding showed that HER2 positivity is slightly falling in the range of reported literatures (15-30%) [8,[30][31][32][33][34]. For instance, Borgquist et al [33] [30].…”
Section: Discussionmentioning
confidence: 62%